Toward an Explanation of Variations in Teachers’ Perceptions of Teacher Leadership - Liu, Peng; Liu, Lili; Adeniji, Rosheedat (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
The purpose of this study is to understand how teachers’ perceptions of teacher leadership are formed in education practice. Based on information processing theory and findings from 873 teachers in Chinese schools, this article provides an explanation of the formation of teachers’ leadership perceptions as a function of both alterable variables within the school context and unalterable characteristics of both leaders and followers. It is concluded that alterable school conditions explain most of the variations in teachers’ perceptions of teacher leadership. The study proposes the theoretical implication that alterable variables were more powerful in the development process of teachers’ perceptions of teacher leadership. In addition, the findings indicate that school principals can control organizational factors to enhance teachers’ perceptions of teacher leadership to improve the effectiveness of leadership.